2020
DOI: 10.1002/ps.5807
|View full text |Cite
|
Sign up to set email alerts
|

Dual ecosystem services of syrphid flies (Diptera: Syrphidae): pollinators and biological control agents

Abstract: With increasing worldwide pressure on bee pollinator populations and an increase in insecticide resistance amongst pest insects, there is a growing need for diversification of pollinator and pest control systems. Syrphid flies (Diptera: Syrphidae) contribute ecosystem services to agroecosystems through their supporting roles as crop pollinators and predators of pests. Adult syrphids are important pollinators with high floral visitation rates and pollen carrying capacity, while predatory syrphid larvae are natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
119
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(126 citation statements)
references
References 74 publications
4
119
1
2
Order By: Relevance
“…The use of chemical ecology to manage insect parasitoids that have parasitoid hosts (fourth tropic level hyperparasitoids) is reviewed 15 . There is a review on the potential use of syrphid flies as pollinators and biological control agents 16 . How climate change can affect insecticide resistance and its genetics is reviewed 17 .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The use of chemical ecology to manage insect parasitoids that have parasitoid hosts (fourth tropic level hyperparasitoids) is reviewed 15 . There is a review on the potential use of syrphid flies as pollinators and biological control agents 16 . How climate change can affect insecticide resistance and its genetics is reviewed 17 .…”
Section: Figurementioning
confidence: 99%
“…15 There is a review on the potential use of syrphid flies as pollinators and biological control agents. 16 How climate change can affect insecticide resistance and its genetics is reviewed. 17 The structure, function, activation, specificity, and mode of action of the insect-active proteins produced by Bacillus thuringiensis in its vegetative stage are discussed.…”
mentioning
confidence: 99%
“…Recently, it was demonstrated that two commercially available hoverflies, namely Eupeodes corollae (Fabricius) and Sphaerophoria rueppellii (Wiedemann), could control the aphid Myzus persicae (Sulzer) (Hemiptera: Aphididae) and concurrently contribute to pollination in sweet pepper 13 . Yet important gaps still exist regarding the potential of these species to effectively regulate populations of other important aphid pests in augmentative biological control programs 1 …”
Section: Introductionmentioning
confidence: 99%
“…The pollen is more attractive to wild bees than honey bees. There are two possible solutions: (a) Release of pollinators other than honey-bees and bumblebees, such as syrphids [8], since the flowers of tomato are widely visited by hoverfly species [9,10]. (b) Supplying of additional food to pollinators in order to maintain more adult insects than what is maintained by greenhouse crops [11,12].…”
Section: Introductionmentioning
confidence: 99%